1995
DOI: 10.1051/lait:1995640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forage type on milk yield, Chemical composition and clotting properties of milk

Abstract: Summary -Fifty-Iour lactating multiparous cows were used in a 3 x 3 latin square trial. During each 3-week period cows were offered a diet composed either 01 perennial ryegrass silage (11 kg dry matter/dl, or second-cutting cocksloot hay (13 kg dry matter/dl or maize silage (11 kg dry matter/dl. Each diet was supplemented with a mixture 01 barley, soya-bean meal and urea in proportions calculated to keep the overall rations isocaloric and isonitrogenous. The cows led grass silage yielded, respectively, 0.4 (P>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
1
16
2
2
Order By: Relevance
“…This trial confirmed the beneficial effect of grass silage-based diets on milk production to the detriment of milk solids concentration, as already reported relative to hay (Journet and Dulphy, 1973;Burstedt and Lingvall, 1977;Coulon et al, 1995) or maize silage (Verite and Joumet, 1971 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This trial confirmed the beneficial effect of grass silage-based diets on milk production to the detriment of milk solids concentration, as already reported relative to hay (Journet and Dulphy, 1973;Burstedt and Lingvall, 1977;Coulon et al, 1995) or maize silage (Verite and Joumet, 1971 ).…”
Section: Discussionsupporting
confidence: 87%
“…The differences in performances between hay-and silage-based diets rationed to provide the same amount of energy and protein are generally ascribed to a different distribution of energy between milk production and body reserves, as well as to a dilution effect of secreted milk solids (Journet and Dulphy, 1973;Coulon et al, 1995). In this trial, contrary to that which we observed previously, it would appear that the majority of the differences observed were due to a dilution effect of secreted milk solids.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…It should also be noted that the composition and physico-chemical characteristics of milk varies significantly between species and even between races (Soryal et al, 2004). These characteristics are also dependent on the nature of the feed (Sutton, 1989;Coulon et al, 1995.). Dairy products are considered nutrient-rich foods.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies (Wyss and Collomb, 2011;Mc Cormick et al 2011) suggested that cows fed either silage or dry hay resulted in similar milk yield and milk composition, others (Coulon et al 1995;Coulon et al 1997;Borreani et al 2007) reported that milk production of the dairy cows fed silage were higher than that of animals received diets based on dry hay as roughage. On the contrary of all these findings, Broderick (1995) indicated that yields of milk and fat corrected milk and percentage of milk components were greater on the all hay group than on the all silage diet without added protein supplement.…”
Section: Introductionmentioning
confidence: 99%